Chronic Sinusitis Associated with Turbinate Hypertrophy and Septal Deviation in a 63-Year-Old Patient (Revista de Medicina Clinica, 2024)
Chronic sinusitis is a common pathology in otorhinolaryngology practice, often associated with turbinate hypertrophy and septal deviation, especially in older adults. Statistically, it is estimated that septal deviation affects approximately 80% of the population to some extent, increasing the risk of chronic nasal obstruction and complications such as recurrent sinusitis, particularly in individuals exposed to nasal trauma or with chronic rhinitis. Both turbinate hypertrophy and nasal septum deviation contribute to a significant alteration in airflow and hinder the adequate drainage of secretions, thus promoting chronic inflammation of the nasal mucosa. In this context, we present the clinical case of a 63-year-old male patient with chronic sinusitis associated with turbinate hypertrophy and septal deviation. This case highlights the close relationship between these conditions and their negative impact on the patient’s quality of life, underscoring the importance of timely diagnosis and treatment to relieve symptoms and prevent long-term complications.
Keywords: Nasal Cavity; Nasal Turbinates; Sinusitis; Nasal Septum